TOWARDS PERSONALIZED TREATMENT OF DEPRESSION - M. Y. Gerasimchuk (Архивъ внутренней медицины)
Disruption of biological rhythms is a relevant factor contributing to the etiology and pathogenesis of depression. This review provides the evidence of desynchronization in the clinical presentation of onset and relapse. The results of own study revealing frequency of sleep disturbances and effects of seasonality on depression risk are presented. According to chronobiology, the current opportunities and promising directions of personalized therapy development are considered.